Severe hypoglycemia caused by a small dose of repaglinide and concurrent use of nilotinib and febuxostat in a patient with type 2 diabetes - Komatsu, Hitomi (Diabetol Int, 2020)
Repaglinide, an oral hypoglycemic agent, is a short-acting insulin secretagogue. We describe a case, in which an extremely low dose of repaglinide caused severe hypoglycemia and novel drug interactions are suggested. A 71-year-old man with type 2 diabetes was taken to the hospital due to consciousness disorder caused by severe hypoglycemia. He was taking repaglinide 0.25 mg once in the morning with nilotinib 400 mg/day and febuxostat 20 mg/day. Endogenous insulin secretion was not suppressed even in hypoglycemia. Detection of plasma repaglinide 10 h after administration in this case indicates delayed elimination of the agent, which might be derived from reduced hepatocyte uptake due to inhibitory effects of nilotinib on OATP1B1 and reduced oxidation of the agents by inhibitory effects of nilotinib, mainly on CYP3A4 activities, and of febuxostat on CYP2C8 activities. Repaglinide is eliminated by the liver, and is a short-acting insulin secretagogue with a good safety profile in patients with type 2 diabetes complicated by renal impairment, including elderly patients; however, its delayed elimination due to drug–drug interactions should be noted.